Clinical characteristics and risk factors for readmission after deep anterior lamellar keratoplasty: a nationwide, cross-sectional, multicenter study - Chenxi Wang; He Xie; Binjia Sun; Kexin Tang; Haiou Wang; Zelin Zhao; Qinxiang Zheng; Jie Wu; Qi Zhang; Baihua Chen; He Dong; Jizhong Yang; et al. (BMC Ophthalmology)
Abstract Background To assess the incidence, cause and risk factors for unplanned readmission within 90 days after deep anterior lamellar keratoplasty (DALK). Methods A multicentre cross-sectional study of 3603 eyes of 3588 patients after keratoplasty between January 1st, 2019, and September 30th, 2021 in 16 hospitals across China was performed. The demographic and clinical features between patients after DALK with 90-day unplanned readmission and those who did not have been compared. The risk factors of unplanned readmission were identified by a multivariable Cox regression model. Results Among 873 patients (878 eyes) after DALK, and the primary indications for DALK were keratitis (391 eyes, 44.53%) and keratoconus (275 eyes, 31.32%). The rates of unplanned readmission within 30 days, 60 days, and 90 days were 1.95%, 4.01%, and 5.15%. The main reason of 90-day readmission was infectious keratitis (18 eyes, 40.00%), followed by corneal epithelial defects (11 eyes, 24.44%) and immune-related keratitis (10 eyes, 22.22%). Patients readmitted within 90 days exhibit a more advanced age (p = 0.013). It is also more concentrated in patients with corneal ulcers or perforations (p = 0.029) or blindness (p = 0.02). Compared with patients with keratoconus, patients with keratitis (HR = 3.545, 95% CI 1.104–11.386, p = 0.034) and corneal degeneration or malnutrition (HR = 6.470, 95% CI 1.942–21.560, p = 0.002) are more likely to have an unplanned readmission risk within 90 days. Conclusion The main causes of unplanned readmission within 90 days after DALK were infectious keratitis, corneal epithelial defects, and immune-related keratitis. The indications for DALK were associated with 90-day readmissions. Clinical trial number Not applicable.